De plaats van de toeschouwer: Theoria, religie & theologie in de moderne tijd - Bocken, Inigo (Tijdschrift voor theologie, 2009)
This article argues for elucidation of the difference between religion and the question of God in modern society. The external positioning of academic observation is doubtless one of the core characteristics of the modern academic paradigm. There is ambiguous tension between this and the internal claims of various types of religious life. This essay posits that this tension is not restricted to religion, but is a fundamental characteristic of modern culture and all scholarly endeavour. There is a growing awareness that the neutral eye of (religious) sciences must face up to blind spots. The essay suggests this issue be thematically developed using a genesis of the theory paradigm. A brief history of the concept theory shows that in addition to the observer’s place playing a key role from the earliest days, the development of theoretical viewing also coincided with a change to the observer’s position. At the end of the Middle Ages, there was a growing awareness that the observer, in a manner of speaking, stood in his own way when it came to observing (theory as seeing God). One important strategy in modern (philosophical, theological and scholarly) study was to focus on the observer and what he saw. Pavel Florensky’s intriguing theory of reverse perspective shows that this strategy no longer worked in the late modern period or that it became entangled in internal contradictions. Florensky’s theory is aimed at the observer’s participation in the image’s reality. This participation is grounded in Orthodox religious iconostasis. This theory is paradigmatic for late modern - reactionary - tendencies to update the meaning of the question of God for culture while relying on a specific religious system. This, the essay asserts, repeats the problem of the modern observer trapped in himself. This time the divine view is recorded. That is why, toward the end, the essay makes the (open) suggestion to differentiate the question of God sharply from religion and to understand it as an exploration of the blind spots operational in every functional system. Theory then becomes a paradigm that seeks the ruptures and blind spots that seem to occur in every observation system.